Professors in the boardroom and their impact on corporate governance and firm performance - Bill Francis; Iftekhar Hasan; Qiang Wu (Bank of Finland, 2014)
Directors from academia served on the boards of around 40% of S&P 1,500 firms over the 1998-2011 period. This paper investigates the effects of academic directors on corporate governance and firm performance. We find that companies with directors from academia are associated with higher performance and this relation is driven by professors without administrative jobs. We also find that academic directors play an important governance role through their advising and monitoring functions. Specifically, our results show that the presence of academic directors is associated with higher acquisition performance, higher number of patents and citations, higher stock price informativeness, lower discretionary accruals, lower CEO compensation, and higher CEO forced turnover-performance sensitivity. Overall, our results provide supportive evidence that academic directors are valuable advisors and effective monitors and that, in general, firms benefit from having academic directors.
URN:NBN:fi:bof-201410313102
Keywords: 330